Cell cycle kinase CHEK2 in macrophages alleviates the inflammatory response to Staphylococcus aureus-induced pneumonia. (7th February 2022) - Xie, Fei; Chen, Ruidong; Zhao, Jie; Xu, Chunyan; Zan, Chunxiang; Yue, Bin; Tian, Wenqiu; Yi, Wenxia
Abstract: Background: Excessive macrophage-mediated inflammation participates in the development of Staphylococcus aureus ( S. aureus )-induced pneumonia. Checkpoint kinase 2 (Chek2) was screened out as macrophage-related infantile pneumonia gene after the differentially expressed analysis of RNAseq data derived from pam3CSK4 stimulated bone marrow-derived macrophages (BMDMs). Methods: RAW264.7 macrophage cells were transfected with Chek2-specific gRNA, which were further overexpressed with wide-type Chek2 or Chek2 kinase activity mutant (Chek2 KD, D368N). At the same time, the relative protein and mRNA expression of inflammatory cytokines were determined. C57BL/6J WT mice were intranasally infected with S. aureus to induce S. aureus -induced pneumonia, which was treated with BML-277, an inhibitor of Chek2. The symptoms of pneumonia mice and inflammatory cytokines associated with the nuclear factor kappa B (NF-κB) signaling pathways were further examined. Results: In vivo, BML-277 significantly promoted pneumonia symptoms, including mortality, lung infiltration of immune cells, and the abundance of lung pro-inflammatory cytokines. Mechanically, BML-277 did not affect BMDMs survival but up-regulated the mRNA expression of tumor necrosis factor (Tnf), nitric oxide synthase 2 (Nos2), interleukin (Il)23a, and the secretion of Tnf-α and Il-23a. At the same time, genetic complementation experiment testified that Chek2 KD did not inhibit NF-κB and relevant inflammatory cytokines expression. Conclusion: Chek2 functions through the kinase mechanism to down-regulate the NF-κB pathway in macrophages to alleviate S. aureus -induced pneumonia in mice.